Almespar: An Open Reading Frames Detection Tool Using Python - Osamah Alrouwab; Ismail Mallian; Buthaynah Ramadhan; Kareemah Abdullah; Omiema Aznad; Abd Almajid Abu khashim; Mahmoud Gargotti (AlQalam Journal of Medical and Applied Sciences, 2023)
Background and aims. Open reading frames (ORFs) are sections of a reading frame that do not include any stop codons. A reading frame is a sequence of nucleotide triplets read as codons indicating amino acids; a single strand of DNA has three potential reading frames. Long ORFs in a DNA sequence may represent possible protein-coding areas. In addition to extended ORFs, which assist in gene locus prediction, there is yet another type of ORFS known as small open reading frames (smORFs), which have 100 codons or fewer. Methods. We develop an offline, cross-platform, and dependable detection tool for regular ORFs and smORFs prevalent in biomedical studies. Results. In this work, the most ORFs were found in the Bos taurus (Cattle) Insulin gene, which had 17 consecutive ORFs, while the fewest ORFs were reported in the Cani’s lupus (Dog) Insulin gene, which had only 4 ORFs. Conclusion. The software meets the expected demarcation restrictions. We strongly advise more research into the detection of nested ORFs.